The Development of The Professional Training of A Future Music Teacher And The Factors Influencing It - Mamasoliyevna, Normurodova (Indonesian Journal Publisher, 2025)
The musical and educational process and its results depend on the working methods that determine the educator's effect on the educator's cognitive activity. For this reason, it has always been considered in pedagogy that teaching methods are methods of educating a teacher and methods of cognitive activity of a teacher, both of these methods are used to perform educational functions. Educational methods determine the nature of the educators' activities. They will depend on the purpose of education. The tradition of mentoring plays an important role in developing the practical competence of future music teachers.